2010
DOI: 10.1007/s00442-010-1595-3
|View full text |Cite
|
Sign up to set email alerts
|

Why only tetraploid Solidago gigantea (Asteraceae) became invasive: a common garden comparison of ploidy levels

Abstract: Many studies have compared the growth of plants from native and invasive populations, but few have considered the role of ploidy. In its native range in North America, Solidago gigantea Aiton (Asteraceae) occurs as a diploid, tetraploid and hexaploid, with considerable habitat differentiation and geographic separation amongst these ploidy levels. In the introduced range in Europe, however, only tetraploid populations are known. We investigated the growth performance and life history characteristics of plants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 53 publications
8
82
2
1
Order By: Relevance
“…Solidago gigantea occurs in three different cytotypes: diploid (2n = 18), tetraploid (2n = 36) and hexaploid (2n = 54), which represent the whole S. gigantea complex in native range and has also been found in Europe [16]. However, according to current data [17][18][19] in Europe only tetraploid populations of S. gigantea are known. Therefore, based on this variety in chromosome number, considerable morphological variety in these taxa could be expected [20].…”
mentioning
confidence: 98%
“…Solidago gigantea occurs in three different cytotypes: diploid (2n = 18), tetraploid (2n = 36) and hexaploid (2n = 54), which represent the whole S. gigantea complex in native range and has also been found in Europe [16]. However, according to current data [17][18][19] in Europe only tetraploid populations of S. gigantea are known. Therefore, based on this variety in chromosome number, considerable morphological variety in these taxa could be expected [20].…”
mentioning
confidence: 98%
“…Another is that other ploidies had been also introduced, but they failed to establish or expand its ranges. Studies of the ploidy level of S. gigantea in the invasive and native range revealed that tetraploids were more invasive than diploids, and it was the only cytotype found in the invasive range (Schlaepfer et al 2008(Schlaepfer et al , 2010. Future research on population genetics and common garden experiments is necessary to evaluate the potential evolutionary dynamics of S. altissima after introduction.…”
Section: Resultsmentioning
confidence: 99%
“…In its invasive range in Europe and East Asia, only tetraploid plants are found (Schlaepfer et al 2008(Schlaepfer et al , 2010). Studies on the ploidy level of S. gigantea in Lithuania also proved all plants to be tetraploids (2n=36) (Karpavičienė & Radušienė 2016).…”
Section: Discussionmentioning
confidence: 99%